Economic Valuation of Soil Erosion and Sedimentation in Cameron Highlands - Chew, Chang Guan (1999)

(untitled)
This study was conducted primarily to determine and quantify the costs associated with soil erosion (on-site costs) and sedimentation (off-site costs) in Sungai Ikan Catchment, Cameron Highlands. Data used on rate of sediment yield in the area was obtained from a study of Baharuddin et.al., 1996. The average sediment yield in the Sungai Ikan Catchment was estimated to be 19.7 mt/halyear. The on-site cost estimation revealed that a hectare of soil loss in a year is worth RM8178.62, which is the forgone net revenue of the farmer. The on-site cost is about 9.16% of the production cost of vegetable production. The total on-site cost due to erosion in Sungai Ikan Catchment is more than RMl8.3 million for 18 years. For calculating the off-site costs, the incremental cost to TNB due to sedimentation is used. It shows that every metric tonne of sediment from Sungai Ikan Catchment incurred RM171.69 extra cost to TNB. The incremental cost due to sedimentation is about 10.09010 of the total net revenue to TNB. The incremental off-site cost to Society, which taking into account the benefit of selling sand and the differential cost of electric to TNBG, the total incremental off-site cost to society is RM72.5 million for 18 years. The finding of this study could hopefully serve as a useful guide to the local authority in the preparation of land development and other parties who needed it. Implications of this finding for soil erosion and suggestions are discussed.